Pengaruh Keterikatan Karyawan Dan Motivasi Intrinsik Terhadap Kinerja Karyawan (Studi Pada Karyawan Pt. Einstrend Factory 3 Departemen Sewing Purwakarta): Employee Engagement, Intrinsic Motivation, Employee Performance - Patoni, Patoni; Mawardi, Amna; nurjanah, rere (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
This research was conducted at PT. Einstrend Factory 3 Sewing Department with the aim of researching the effect of employee engagement and intrinsic motivation on employee performance. The research model used is quantitative and the method used is descriptive verification with multiple linear regression analysis. The number of research samples is 89 respondents. The results showed that partially employee engagement and intrinsic motivation had a positive and significant effect on employee performance. Simultaneously showed a significant influence between employee engagement and intrinsic motivation on employee performance of 58.2% and the remaining 41.8% was influenced by other factors not examined by researchers.